Aplasia Cutis Congenita Associated with the Use of Antithyroid Medications during Pregnancy: A Case Report - Pham Chi Kong; Huynh Nhat; Le Chi (Mashhad University of Medical Sciences, 2022)
Background: Aplasia Cutis Congenita (ACC) is a rare malformation characterized by localized congenital absence of the skin which was first described by Cordon in 1767. ACC is estimated to occur in approximately 1 to 3 cases in 10000 live births. Many factors can contribute to developing ACC among which antithyroid medications were the strongest risk factor. A total of 61 cases of ACC were reported due to Methimazole/Carbimazole.Case report: We report a female infant with ACC whose mother received Methimazole during pregnancy. Two small, punch-out lesions of the scalp were observed in diameters from 1.5 cm to 2 cm. The patient was treated with conservative care. Crusting and scab formation began on the fifth day. Minor, atrophied and hairless scars were found at the previous location of lesions by reexamining after 12 months.Conclusion: The etiology of ACC has not yet been clearly defined. Methimazole may be a factor associated with this disorder. Management of ACC includes conservative care and surgery depending on the location and size of lesions, associated anomalies, and health of the infant.